Fetal echocardiography in detecting anomalous pulmonary venous connection: four false positive cases. Issue 4 (April 1995) - Papa, M.; Camesasca, C.; Santoro, F.; Zoia, E.; Fragasso, G.; Giannico, S.; Chierchia, S. L.
Abstract : Prenatal detection of congenital heart disease is possible from the 16th week of pregnancy, the ideal time being the mid-trimester, when most cardiac abnormalities can be detected. However, identification of anomalous pulmonary venous connection is difficult before birth and the sensitivity of fetal echocardiography in detecting this anomaly is low. Four cases are reported in which fetal echocardiographic findings obtained during the third trimester of pregnancy were highly suggestive of anomalous pulmonary venous connection. Right ventricular and atrial dominance associated with an enlarged coronary sinus or dilated superior vena cava were identified and considered to be indirect markers of the anomaly. No other cardiac anomaly was detectable. In all cases right ventricular and atrial dominance with dilated coronary sinus or superior vena cava were confirmed after birth despite the presence of normal pulmonary venous connections. These results confirm that the prenatal detection of this condition is difficult and should be based on the direct visualisation of anomalous pulmonary venous connections. The sole detection of indirect signs, such as right atrial and ventricular dominance with or without a dilated coronary sinus, superior vena cava, or inferior vena cava, does not warrant the diagnosis of anomalous pulmonary venous connection. Since the pulmonary venous flow in the human fetus is not as small as is commonly assumed, an anomalous drainage should be detectable when present and therefore should be specifically sought if the anomaly is suspected. The reasons for the presence of such transient cardiac anomalies remain obscure, but they might be related to functional or morphological rearrangement of the heart during fetal and perinatal life.